Ablation of persistent atrial fibrillation: Challenges and solutions. (18th December 2019) - Terricabras, Maria; Piccini, Jonathan P.; Verma, Atul
Abstract: Catheter ablation is commonly used for treatment of persistent atrial fibrillation (AF). Pulmonary vein isolation (PVI) is still the cornerstone for the procedure, however, outcomes are consistently lower compared to paroxysmal AF. It is hypothesized that it could be due to lack of durable lesions or the presence of non‐PV targets that remain after PVI. Numerous advances in ablation catheter technologies and mapping systems may potentially achieve lower recurrence rates in the future. Ongoing research is required to discover the best technique for persistent AF ablation. The purpose of this review is to describe the new, developing technologies that may improve the outcome of this procedure in the persistent AF population.